Determination of Trace Element Mass Fractions in Ultramafic Rocks by HR‐ICP‐MS: A Combined Approach Using a Direct Digestion/Dilution Method and Preconcentration by Coprecipitation. Issue 1 (30th September 2017) - Rospabé, Mathieu; Benoit, Mathieu; Candaudap, Frédéric
Abstract : A procedure is described for the determination of thirty‐seven minor and trace elements (LILE, REE, HFSE, U, Th, Pb, transition elements and Ga) in ultramafic rocks. After Tm addition and acid sample digestion, compositions were determined both following a direct digestion/dilution method (without element separation) and after a preconcentration procedure using a double coprecipitation process. Four ultramafic reference materials were investigated to test and validate our procedure (UB‐N, MGL‐GAS [Geo PT 12], JP‐1 and DTS‐2B). Results obtained following the preconcentration procedure are in good agreement with previously published work on REE, HFSE, U, Th, Pb and some of the transition elements (Sc, Ti, V). This procedure has two major advantages: (a) it avoids any matrix effect resulting from the high Mg content of peridotite, and (b) it allows the preconcentration of a larger trace element set than with previous methods. Other elements (LILE, other transition elements Cr, Mn, Co, Ni, Cu, Zn, as well as Ga) were not fully coprecipitated with the preconcentration method and could only be accurately determined through the direct digestion/dilution method. Key Points: Thirty‐seven minor and trace elements are investigated in four reference materials (UB‐N, MGL‐GAS, JP‐1 and DTS‐2B). A double co‐precipitation method appears to be suitable for the determination of REE, HFSE, U, Th, Pb, Sc, Ti and V in ultradepleted peridtotites. Other LILE, transition elements and Ga can be determined only following a standard digestion/dilution method.